Kırımlı (Ebubekir) Rif’at Efendi / Abu Bakr Rifat Efendy The Crimean - UZUN, Adnan (Journal of History Culture and Art Research, 2013)
Özet Rif’at Efendi 19.Yüzyıl Divan şairlerindendir. Hayatı hakkında yeterli bilgi yoktur. Kırım’da doğmuş, küçük yaşta Anadolu’ya gelmiş, burada kendini yetiştirmiştir. Ailesi hakkında ve nasıl yetiştiği konusunda bilgi yoktur. Anadolu’da sıkıntılı bir hayat sürmüş, çeşitli devlet adamlarının kâtipliği görevine getirilmiştir. Kendisi hayatta iken vefat eden iki kızı ve iki oğlu vardır. Münşeat ve şiirlerden oluşan taş baskı tekniği ile basılmış eseri vardır. Abstract Rif’at Efendy is one of the Divan’s poets of 19th century. There isn’t sufficient knowledge about his life in the sources. He was born in Crimea, came to Anatolia in his young ages and he has educated himself. There is not any knowledge about his family and how he grew up. He lived a life which is troublesome, he has charged with clerkship of various statesmen. He had two sons and two daughters who died when he was alive. He has a work that consists of Münsand proses which is published with technique of lithography.